ON BOUNDED OPERATORS IN L^p SPACES - Petrosyan, A.I.; Beknazaryan, A.F. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
In the present paper the linear operators that depend on a normal pair of weight functions {φ, ψ,} in the Banach spaces L^p(D), where D is the unit disk in the complex plane, are considered. It is investigated, for which values of p these operators are bounded.